Vaccine effectiveness of tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis vaccine during a pertussis outbreak in Maine. Issue 22 (11th May 2016) - Terranella, Andrew; Rea, Vicki; Griffith, Matthew; Manning, Susan; Sears, Steven; Farmer, Ann; Martin, Stacey; Patel, Manisha
Abstract: Background: Multiple school-associated pertussis outbreaks were reported in Maine from 2010 to 2011. These outbreaks were associated with an overall increase in pertussis cases statewide. Waning of protection in students recently vaccinated with tetanus, diphtheria, and acellular pertussis (Tdap) has been implicated in the increase in reported rates of pertussis nationally. Methods: We conducted a retrospective cohort study to evaluate Tdap vaccine effectiveness (VE) among students aged 11–19 years in two schools reporting outbreaks in 2011. All pertussis cases reported from August through November, 2011 at the two schools were included. Vaccination history was verified using provider information, state vaccine registry data, and parental verification. Attack rates (AR) were calculated. VE and duration of protection was calculated as VE = 1 − (ARvaccinated /ARunvaccinated ) × 100% using a log binomial regression model. Results: Of 416 students enrolled, 314 were included in the analyses. Twenty-nine cases collectively in Schools A and B. Tdap coverage was 65% at School A and 42% at School B before the start of the outbreak. Among students enrolled in the study, attack rates were 11.9% and 7.7% at Schools A and B, respectively. Overall VE was 68.5% (95% confidence interval (CI) 37.7–86.2). VE was 70.4% (95% CI 17.5–89.4) for School A and 65.2% (95% CI −19.2 to 89.9) for School B. VE <2 years versus ≥2 years from outbreak onset was not significantly different. Conclusions: Tdap was moderately effective in preventing disease among vaccinated students. Vaccine coverage of 65% or less was suboptimal and might contribute to outbreaks. Waning VE was not demonstrated. Increased vaccination coverage rates as well as further evaluation of the role of acellular vaccine on VE is needed.